Cognitive Behavioral Therapy Spritualitas Islam Untuk Mengatasi Kecemasan Sosial Remaja - Abi Apriyadi (Counselle| Journal of Islamic Guidance and Counseling, 2022)
Abstract This paper aims to describe the principles and techniques that can be developed through the cognitive behavioral therapy approach with Islamic Sprituality. Integrating Islamic values into the Cognitive Behavioral Therapy approach is expected to help adolescents who experience social anxiety that does not lead to unwanted conditions such as depression ad so on. There are several Cognitive Behavioral Therapy interventions for Islamic sprituality by integrating Islamic Values, which can be done by utilizing Islamic religious resources such as religious practices, opposing irrational thoughts, interpreting verses of the Qur’an and contemplative prayers. This is an effort to raise awareness of the wrong way of thinking and behavior in the pattern of social life. Social anxiety is a condition that causes individuals to be ashamed and afraid and have negative thoughts when dealing with social situations. This condition occurs as a result of cognitive and affective responses that cannot be controlled properly which then makes individuals avoid themselves from social interactions. KEYWORD: Cognitive Behavior Therapy, Islamic Sprituality, Social, Anxiety. Abstrak Tulisan ini tujuannya untuk mendeskripsikan terkait prinsip dan teknik yang dapat dikembangkan melalui pendekatan Cognitive Behavioral Therapy dengan spritualitas Islam. Mengintegrasikan nilai-nilai Islam pada pendekatan Cognitive Behavioral Therapy diharapkan agar membantu remaja yang mengalami kecemasan sosial agar tidak mengarah kepada kondisi yang tidak diinginkan seperti depresi dan lain sebagainya. Ada beberapa intervensi Cognitive Behavioral Therapy spritualitas Islam dengan mengintegrasikan nilai-nilai Islam dapat dilakukan dengan cara memanfaatkan sumber daya agama Islam seperti praktek keagamaan, menentang pikiran tidak rasional, memakni ayat al-Qur’an dan do’a secara kontempatif. Hal ini sebagai upaya untuk menyadarkan cara beprikir serta perilaku yang keliru pada pola kehidupan sosialnya. Adapun kecemasan sosial suatu kondisi yang menyebabkan individu malu dan takut serta memiliki pikiran yang negatif ketika akan berhadapan dengan situasi sosial. Kondisi ini terjadi akibat dari respon kognisi dan afeksi tidak dapat terkendali dengan baik yang kemudian membuat individu menghindari dirinya dari interaksi sosial. KATA KUNCI: Cognitive Behavioral Therapy, Spritualitas Islam, Kecemasan Sosial.